Sejarah, Transformasi, dan Adaptasi Lembaga Pendidikan Islam di Indonesia - Enhas, Muhammad Iqbal Ghifari; Zahara, Alfan Nawaziru; Basri, Basri (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
This article discusses the existence of Islamic education in Indonesia which was born from the treasures of civilization and the development of Islam in the archipelago. This research uses a descriptive qualitative approach based on library research. The results of analysis show that traditional Islamic educational institutions such as dayah in Aceh, surau in Minangkabau, langgar in Madura, and pesantren throughout the archipelago are an integral part of Islamic education in Indonesia. On the other hand, the influence of modern culture brought by the Dutch colonial government also had a significant impact on the dynamics of the development of Islamic educational institutions. The awareness of the Indonesian Muslim community on the importance of the development of modern education brings transformation and adaptation in Islamic educational institutions. The emergence of elite Islamic schools is part of the dynamic development of contemporary Islamic education in Indonesia. These elite Islamic schools reflect changes in the landscape of Islamic education, where Islamic education previously represented by traditional educational institutions such as surau, madrasah, and pesantren is experiencing modernization implications.